Freedom and its manifestations in the poetry of Muhammad Abdo Ghanem - Baharvand, Vali (Journal of Human Sciences, 2023)
The occurrence of various political and social events and the literary revolution in the twentieth century with the aim of achieving freedom led to a sense of responsibility towards society. Muhammad Abdo Ghanem is one of the poets who reflected the manifestations of freedom in his poetry, and depicted important contents such as the call for unity and the defense of Palestine, and the call for awakening and anti-colonialism, and expressed deep and valuable ideas in its light. The aim of this analytical-descriptive research is to study the manifestations of freedom in the poetry of Muhammad Abdo Ghanem and to identify high and valuable concepts in their light. One of the most important findings of this article is that the poet has never forgotten the suffering of the Yemeni people and that he called the Mujahideen for freedom to defend and fight the enemy, as he refers to the glorious past of Islamic civilization, along with guiding Muslims to awakening and unity He avoided any backwardness and that colonialism is trying to stifle the voice of the militants and neglect them with various tools such as imprisonment and encourages in his poetry the Arabs to fight the Zionists on the one hand, and on the other hand, the weakness of the Arab leaders is the main cause of their misery.